2019
DOI: 10.1097/ico.0000000000002085
|View full text |Cite
|
Sign up to set email alerts
|

Did Collagen Cross-Linking Reduce the Requirement for Corneal Transplantation in Keratoconus? The Canadian Experience

Abstract: Purpose: To investigate the relationship between corneal collagen cross-linking (CXL) and the number of corneal transplants required for the treatment of keratoconus (KCN) in 2 major Canadian provinces. Methods: This is a retrospective review of all corneal transplantation performed in Ontario and British Columbia over an 18-year period (1998–2016). Data were collected at the Eye Bank of Canada—Ontario/British Columbia Divisions. The primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A Canadian study found a significant decrease in the proportion of total corneal transplants performed for keratoconus but no change in the absolute numbers of grafts performed for keratoconus, and therefore, was believed to represent an increasing demand for endothelial keratoplasty rather than a decrease in requirement for keratoconus 25 ; however, this study did not normalize data to account for population growth. Normalizing the number of transplants per year and per population in NZ and performing piecewise analysis suggest that we are beginning to see the beneficial effects of CXL on keratoconus-related transplantation.…”
Section: Discussionmentioning
confidence: 75%
“…A Canadian study found a significant decrease in the proportion of total corneal transplants performed for keratoconus but no change in the absolute numbers of grafts performed for keratoconus, and therefore, was believed to represent an increasing demand for endothelial keratoplasty rather than a decrease in requirement for keratoconus 25 ; however, this study did not normalize data to account for population growth. Normalizing the number of transplants per year and per population in NZ and performing piecewise analysis suggest that we are beginning to see the beneficial effects of CXL on keratoconus-related transplantation.…”
Section: Discussionmentioning
confidence: 75%
“…Although other studies have reported a significant decrease in the proportion of corneal transplants for KC, this was because of an increase in the number of endothelial keratoplasties rather than a decrease in the absolute number of transplants. 42,43 Furthermore, although CXL was introduced in Europe 20 years ago, KC remains the most common cause of corneal transplants in many regions. [44][45][46] Reports have found a reduction in the number of keratoplasties for KC, suggesting that improved contact lens technology is the main reason for this reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, a novel treatment known as corneal collagen crosslinking was introduced, effectively strengthening the cornea and stabilizing the disease [ 8 ]. This treatment has globally reduced the need for corneal transplantation, as recent data indicates [ 9 - 10 ]. Early diagnosis, especially with the availability of cross-linking treatment, is critical to preventing further vision impairment.…”
Section: Introductionmentioning
confidence: 99%